The delivery of cultural care by health professionals among the hospitalized AmaXhosa male initiates of traditional circumcision in the Eastern Cape. - Ntsaba, Mohlomi Jafta. (2010)
Traditional male circumcision is a rite of passage among the AmaXhosa in South Africa. According to the custom of male traditional circumcision, initiates should remain in the bush for the entire seclusion period. The AmaXhosa male initiates encounter complications due to a ritual that has gone wrong. Common complications are penile sepsis, dehydration, penile amputations and septicaemia. As a last resort, when the AmaXhosa male initiates do not improve from complications associated with the custom they are referred to hospital for admission (Meintjes, 1998; Warren-Brown, 1998). The main purposes of this study were, first to explore and describe the delivery of care to the hospitalized AmaXhosa male initiates whilst in the hands of healthcare professionals and professional care system. Second, to describe what constitutes culturally appropriate care for hospitalized AmaXhosa male initiates. This study took place in three research sites, that included one rural hospital and two urban hospitals which admitted the AmaXhosa male initiates of traditional circumcision. A total of 13 hospitalized AmaXhosa male initiates and nine health professionals took part in this study. Leininger's ethnonursing qualitative research approach was used to guide this study. Data were collected, using purposive sampling, by means of unstructured interviews using guides, tape-recorder, and field notes. The study was first piloted at Umlamli Hospital using the same data collecting strategies as for the major study. Data from key and general informants were analysed separately using Leininger's (1991) four-phase method. This was carried out in order to answer the research questions and research purposes. Major themes and patterns emerged from this process. === Thesis (Ph.D.)-University of KwaZulu-Natal, Durban, 2009.